2017
DOI: 10.1186/s12967-017-1163-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary collagen degradation products as early markers of progressive renal fibrosis

Abstract: BackgroundRenal fibrogenesis is associated with increased ECM remodeling and release of collagen fragments in urine in progressive renal disease. We investigated the diagnostic value of urinary collagen degradation products in a proteinuria-driven fibrosis rat model with and without anti-fibrotic S1P-receptor modulator FTY720 treatment.MethodsProteinuria was induced in male Wistar rats by Adriamycin (ADR) injection (n = 16). Healthy rats served as controls (n = 12). Six weeks post-injection, all underwent rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Numerous recent studies have confirmed the association of urinary C3M (uC3M) with renal fibrosis in different rat models including 5/6 Nx, anti-Thy 1.1, adenine nephropathy and type 2 diabetic nephropathy models (Papasotiriou et al 2015;Dower et al 2017). In a proteinuria-driven rat model, uC3M levels were elevated and measurable even before being histologically detectable (Hijmans et al 2017). In type 1 diabetes these markers have not been tested yet and the effect of RAASi treatment on their excretion has not been investigated either.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Numerous recent studies have confirmed the association of urinary C3M (uC3M) with renal fibrosis in different rat models including 5/6 Nx, anti-Thy 1.1, adenine nephropathy and type 2 diabetic nephropathy models (Papasotiriou et al 2015;Dower et al 2017). In a proteinuria-driven rat model, uC3M levels were elevated and measurable even before being histologically detectable (Hijmans et al 2017). In type 1 diabetes these markers have not been tested yet and the effect of RAASi treatment on their excretion has not been investigated either.…”
Section: Introductionmentioning
confidence: 89%
“…In a proteinuria‐driven rat model, uC3M levels were elevated and measurable even before being histologically detectable (Hijmans et al . ). In type 1 diabetes these markers have not been tested yet and the effect of RAASi treatment on their excretion has not been investigated either.…”
Section: Introductionmentioning
confidence: 97%
“…167 Elevated urinary levels of PIIINP were associated with CKDprogression in elderly patients. 168 MMP-mediated collagen I and III degradation fragments, C1M and C3M, were shown to be a potential biomarker in animal models of fibrosis 169,170 and acute kidney injury. 171 In two cohorts of IgA-nephropathy patients, collagen III-turnover suggested a profibrotic ECM remodeling with increasing CKD stage, with steadily increasing Pro-C3 as a marker of collagen III production and progressively decreasing C3M as a marker of collagen III degradation.…”
Section: Renal Ecm Components-biomarker Potential?mentioning
confidence: 99%
“…All these kidney injury markers were highly expressed in the adenine-induced group of rats, whereas these levels were near normal in the rapamycin-treated group. Furthermore, the development of injury would lead to profibrotic and fibrotic events, which are indicated by the increase in uC1M and uC3M, the late renal fibrotic markers [33] that are observed in the urine of the CKD animals.…”
Section: Discussionmentioning
confidence: 99%